TANGGAPAN PENGUNJUNG TERHADAP DAYA TARIK WISATA TAMAN REKREASI STANUM BANGKINANG KABUPATEN KAMPAR - Nurrahmi "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tourist Attraction give more visitation opportunities and needed. A tourist attractionshould be able to develop potential tourist attraction and can increasing the flow of touristvisits. The research proposed to get known how the tourists responses about tourist attractionTaman Rekreasi Stanum Bangkinang Kabupaten Kampar. The research used qualitativedesciptive method to analyze the problems. Samples on the research are 100 samples decidedby slovin. Whereas data collection tecniques took by observation, interview, questionaire, anddocumentacion. And measurement data it was using likert scale to know the length of shortintervals. Based on the research results, tourist responses about tourist attraction with subvariable are uniqueness, authenticity, scarcity, and value of tourist attraction. Of the wholetourist responses about tourist attraction Taman Rekreasi Stanum Bangkinang KabuptaenKampar in every aspect including are enough interesating categories.Keywords :Tourist Attraction, Recreational Park